2021
DOI: 10.15406/bbij.2021.10.00326
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of quota sampling and stratified random sampling

Abstract: The possibility that researchers should be able to obtain data from all cases is questionable. There is a need; therefore, this article provides a probability and non-probability sampling. In this paper we studied the differences and similarities of the two with approach that is more of fritter away time, cost sufficient with energy required throughout the sample observed. The pair shows the differences and similarities between them, different articles were reviewed to compare the two. Quota sampling and Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 3 publications
0
40
0
3
Order By: Relevance
“…Second, this study used quota sampling design with faculty and year as the stratifying factors (i.e., dimensions that formed different groups) instead of a stratified random sampling design. As suggested by Iliyasu and Etikan ( 48 ), using quota sampling may have limitations such as the probability of biased collection of respondents based on invalid quota controls, although it also has the advantages of ease and efficiency and it could be practically used when it is difficult to obtain the population list and engage the potential participants under COVID-19. It is noteworthy that some studies showed that the effectiveness of random sampling was higher than that of quota sampling ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, this study used quota sampling design with faculty and year as the stratifying factors (i.e., dimensions that formed different groups) instead of a stratified random sampling design. As suggested by Iliyasu and Etikan ( 48 ), using quota sampling may have limitations such as the probability of biased collection of respondents based on invalid quota controls, although it also has the advantages of ease and efficiency and it could be practically used when it is difficult to obtain the population list and engage the potential participants under COVID-19. It is noteworthy that some studies showed that the effectiveness of random sampling was higher than that of quota sampling ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Quota sampling was first introduced by Moser and Stuart in experimental research [5] . The quota sampling method is similar to stratified sampling, and it selects a sample from a population that has been divided into subgroups [6] . However, unlike stratified sampling, which relies on the random selection of each subgroup, quota sampling uses a convenience method within each subgroup.…”
Section: Methods Detailsmentioning
confidence: 99%
“…The study adopted a quantitative research approach; it used a stratified random sampling method to collect its data. Iliyasu and Etikan (2021, p. 25) notes that this is a sampling method that involves the division of a chosen group into smaller groups based on homogenous, mutually exclusive segment, from each segment simple random sampling is chosen. In each university; the sampling population was divided into two strata, one group representing undergraduates and another group representing postgraduate students.…”
Section: Research Methodology/designmentioning
confidence: 99%